2015
DOI: 10.1109/lcomm.2015.2392113
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Resource Allocation for Joint Optimization of Energy and Spectral Efficiency in OFDMA Multi-Cell Networks

Abstract: Abstract-The radio resource allocation problem is studied, aiming to jointly optimize the energy efficiency (EE) and spectral efficiency (SE) of downlink OFDMA multi-cell networks. Different from existing works on either EE or SE optimization, a novel EE-SE tradeoff (EST) metric, which can capture both the EST relation and the individual cells' preferences for EE or SE performance, is introduced as the utility function for each base station (BS). Then the joint EE-SE optimization problem is formulated, and an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…Such schemes are, in general, sub-optimal in practice especially in the case of non-uniform user distribution or the case of a large number of cell-edge users. There exists a large body of research conducted in resource allocation for multicell traditional wireless networks, e.g., in [13], [14], [15], [16], [17], [18], [19], [20]. In this type of works, the BS assignment algorithm is separated from the sub-carrier allocation, while joint sub-carrier and power allocation is applied for multicell scenario.…”
Section: B Related Workmentioning
confidence: 99%
“…Such schemes are, in general, sub-optimal in practice especially in the case of non-uniform user distribution or the case of a large number of cell-edge users. There exists a large body of research conducted in resource allocation for multicell traditional wireless networks, e.g., in [13], [14], [15], [16], [17], [18], [19], [20]. In this type of works, the BS assignment algorithm is separated from the sub-carrier allocation, while joint sub-carrier and power allocation is applied for multicell scenario.…”
Section: B Related Workmentioning
confidence: 99%
“…In the work of Jafarizadeh et al [21] it has been shown that the simulation in MS scenarios and usage of linear and random NC reduces latency. In the work of Jing et al [22] it has been shown that by simulation NC reduces the delay in downloading files compared to non-NC applications. Lohne and Weibing [23] illustrate that NC can be used on interactive mobile devices with multiple interfaces.…”
Section: Related Workmentioning
confidence: 99%
“…However, less efforts have been devoted to the research of the energy-efficient multicell resource allocation. An iterative subchannel allocation and power allocation algorithm was proposed in [22] for joint optimization of energy and spectral efficiency. In [23], a distributed resource allocation scheme-based game theory, taking user fairness and priority into consideration, was proposed to solve the energy-efficient RA problem.…”
Section: Related Workmentioning
confidence: 99%